How progress ends : technology, innovation, and the fate of nations - Frey, Carl Benedikt (Princeton University Press, 2025)
In How Progress Ends, Carl Benedikt Frey challenges the conventional belief that economic and technological progress is inevitable. For most of human history, stagnation was the norm, and even today progress and prosperity in the world’s largest, most advanced economies—the United States and China—have fallen short of expectations. To appreciate why we cannot depend on any AI-fueled great leap forward, Frey offers a remarkable and fascinating journey across the globe, spanning the past 1,000 years, to explain why some societies flourish and others fail in the wake of rapid technological change.